Technological Advances in Care of Patients with Kidney Diseases - Saggi, Subodh J.; Salifu, Moro O.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book explores how kidney disease care is being changed by new technologies, from inception and diagnosis to dialysis and kidney transplant. Massive technological advances have affected health care in the past decade, and doctors are moving quickly to change the way we provide care for kidney diseases. We are rapidly shifting from hospital- and clinic-based systems to providing care at home, with technologies that help monitor care and intervene remotely. Some of the technologies covered include genetic testing for diagnostic and therapeutic purposes, metabolism/ezposome assessment, AI-driven tool for drug dosing, and apps available to patients. This book aims to educate providers on the many new scientific and technological interventions that can help monitor and mitigate kidney disease. .
Genetic Testing for the Management of Kidney Disease -- Application of Artificial Intelligence and Machine Learning in Kidney Disease -- The Role of The Metabolism/Exposome In Chronic Kidney Disease: Discovery for Precision Nutrition Microbiome derived Metabolites in CKD and ESRD -- Psychological Factors Associated with Adjustment to Kidney Disease and Engagement in Novel Technologies -- Current Dietary Advances in Enhancing Adherence in ESRD Patients -- Current Strategies to enhance opportunities for ESRD patients to receive a transplant: Sarthak Virmani and Richard Formica -- Blood Pressure Measurement in Chronic Kidney Disease and End Stage Renal Disease Assessing Volume Overload in Patients on Dialysis -- Technologies to monitor dialysis dose, vascular access function, and improve toxin removal -- Technologies Transforming AV Fistula Creation: (3z(BEndo-AVF or Percutaneous-AVF(3y (B-- Delaying the Onset and Progression of CKD in People with Diabetes: Technology and Effectiveness in Achieving Glucose Control -- Strategies and technologies to advance kidney health from Kidney Health Initiative -- Current noninvasive technologies in interventions to control Hyperparathyroid bone diseases of CKD and ESRD -- Sudden Cardiac Death in End Stage Kidney Disease: Technologies for Determining Causes and Predicting Risk -- Current and Future Technologies to Enhance Acceptance of Peritoneal Dialysis -- Project ECHO: Building workforce capacity to improve care for patients with kidney disease -- Use of Artificial Intelligence/Machine Learning for Individualization of Drug Dosing in Dialysis Patients -- Sudden death and coronary artery disease in chronic kidney disease: Strategies to identify and target specific populations.s
Keywords: Nephrology; Nephrology; Kidney Diseases -- therapy; Kidney Diseases -- diagnosis